Selection of Bacillus thuringiensis strains toxic to cotton boll weevil (Anthonomus grandis, Coleoptera: Curculionidae) larvae = Selección de cepas de Bacillus thuringiensis tóxicas para larvas del picudo del algodonero (Anthonomus grandis, Coleoptera: Curculionidae) - Perez, Melisa Paula; Sauka, Diego Hernan; Onco, Maria Ines; Berretta, Marcelo Facundo; Benintende, Graciela Beatriz (Asociación Argentina de Microbiología, 2018)
Preliminary bioassays with whole cultures (WC) of 124 Bacillus thuringiensis strains were performed with neonate larvae of Anthonomus grandis, a major cotton pest in Argentina and other regions of the Americas. Three exotic and four native strains were selected for causing more than 50% mortality. All of them were β-exotoxin producers. The native strains shared similar morphology of parasporal crystals, similar protein pattern and identical insecticidal gene profiles. These features resembled Lepidoptera-toxic strains. Furthermore, these strains showed a Rep-PCR pattern identical to lepidoptericidal strain HD-1, suggesting that these strains may belong to serovar kurstaki. However, some differences were observed in the plasmid profiles and in the production of β-exotoxin. To determine the culture fractions where the insecticidal metabolites were present, bioassays including resuspended spore-crystal pellets, filtered supernatants (FS) were compared with those of WC. Both fractions tested showed some level of insecticidal activity. The results may suggest that the main toxic factors can be found in FS and could be directly correlated with the presence of β-exotoxin. Based on the bioassays with FS and autoclaved FS, the participation of thermolabile virulence factors such as Cry1I in toxicity is neither discarded. In the selected strains, β-exotoxin would be the major associated virulence factor; therefore, their use in biological control of A. grandis should be restricted. Nevertheless, these strains could be the source of genes (e.g., cry1Ia) to produce transgenic cotton plants resistant to this pest.